Keanekaragaman Jenis Gastropoda di Sekitar Tempat Pelelangan Ikan (TPI) Parit 7 Desa Tungkal I Tanjung Jabung Barat (Species Diversity of Gastropods around Parit Fish Auction, Tungkal I Village, West Tanjung Jabung) - NURRUDIN NURRUDIN; Afreni HAMIDAH; Winda Dwi KARTIKA (Biospecies, 2015)
The objective of this research is to determine the gastropod species diversity aroundParit 7 fish auction, Tungkal 1 Village, West Tanjung Jabung. The research found 208 individuals of15 gastropods species: Cerithidea obtusa, Cerithidea alata, Cerithidea cingulata, Telescopiumtelescopium, Telescopium mauritsi, Littoraria melanostoma, Littoraria conica, Littoraria scabra,Nerita balteata, Neritina violacea, Neritina cornucopia, Stramonita gradata, Chicoreus capucinus,Cassidula aurisfelis, and Ellobium aurisjudae. The research concluded that the gastropod speciesdiversity around Parit 7 fish auction Tungkal 1 Village West Tanjung Jabung classified as mediumdue to H' index ranged from 1.79 to 2.28 and there is no dominant species.